Of maps, law, and politics: An inquiry into the changing meaning of territoriality - Friedrich Kratochwil (Danish Institute for International Studies (DIIS), 2011)
This paper examines the changing meaning of 'territoriality' by focusing on the problem of representation. It examines the two-dimensional homogenous space as it has been increasingly used in 'mapping' the international system as an area of mutually exclusive zones of jurisdiction. This way of mapping has reinforced the notion of 'sovereignty' as exclusion, despite the growth of competing jurisdictional claims based on a variety of principles, which the emergence of private international law attempted to mediate during the heydays of the nation state. It also placed international regimes and international organizations 'above' the state where they became 'invisible', thereby again reinforcing the territorial conception of law and politics. The new systems theory of Niklas Luhmann and Gunther Teubner claims to provide a better representation of contemporary social and political reality, as it no longer uses the part/whole distinction as its main conceptual tool and is thus more open to 'legal pluralism' both domestically and internationally. Nevertheless, the conceptualization of autonomous functional systems does not do justice to the special role that law plays in constituting and transforming these supposedly autonomous 'auto-poietic' systems. For that reason the new systems theory fails to address also problems of non-territorial 'imperial' formations as evidenced by the political project of 'governance' and 'best practices', universal human rights, and extra-territorial regulation as exemplified e.g. by the European REACH initiative and the EU's neighborhood policy.
Keywords: 330